Aspetti e tendenze riscontrabili nel repertorio linguistico italiano contemporaneo - Beszterda, Ingeborga (Studia Romanica Posnaniensia, 2007)
The aim of this article is to discuss the fundamental features and the main avenues of the development of the modern Italian language. A great many specialists express their concern over the excessive influence of the spoken language on the morphosyntactic structures of the written language, which is evidenced by, among other things, the use o f repetitions, pleonasms, a lack of discourse coherence as well as rampant use of ready-made expressions copied from the “jargon” used in politics, or the language used by publicists or by bureaucrats. Another problem which is raised by contemporary linguists is the relation between the national language and dialects. Researchers are not in agreement as to the extent to which the Italian language is spread among dialectophones and the mutual influence of these two codes. Finally, attention is drawn to trends in the contemporary Italian language.